Factors influencing perceived value and revisit intention among Vietnamese restaurant consumers - Thi Mai Le; Bao Trung Phan; Viet Trung Dang; Thi Thuy Anh Tran (Zbornik radova Ekonomskog fakulteta u Rijeci : časopis za ekonomsku teoriju i praksu)
The burgeoning smokeless industry faces fierce competition, prompting restaurants to devise effective strategies to satisfy customers and maintain profitability. A study examined factors influencing customers’ perceived value and revisit intentions in restaurants. Analysing data from 211 Vietnamese respondents who dined in the restaurant recently using SPSS version 22 and Smart PLS 3, the research revealed that customer satisfaction directly influences revisit intentions. Moreover, hedonic value and utilitarian values indirectly affect revisit intentions through customer satisfaction. Food and service quality impact hedonic value, with only food quality influencing utilitarian value. Other factors showed weak correlations or were poorly assessed. This study contributes to academia and practice by addressing previous research limitations and providing practical recommendations for restaurant improvement.